2021
DOI: 10.1002/job.2576
|View full text |Cite
|
Sign up to set email alerts
|

When foreign waves hit home shores: Organizational identification in psychological contract breach–violation relationships during international assignments

Abstract: Summary In the context of international assignments, this study investigates the psychological contract breach–violation relationship from a multiparty employment perspective. Multiparty employment refers to arrangements where employees have concurrent psychological contracts with more than one party. Drawing on two waves of survey data from 221 expatriates, we find both direct relationships and asymmetric spillover effects of psychological contract breach on violation. Psychological contract breach by either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…These studies highlight the multi-foci nature of social exchange relationships in which employees can simultaneously hold distinct perceptions toward organizations and each of the various constituencies contained within them ( Reichers, 1985 ; Marks, 2001 ; Lavelle et al, 2007 ). As such, it appears to be plausible that employees may simultaneously perceive an exchange relationship with the organization itself and any or all of these constituencies ( Marks, 2001 ; Conway and Briner, 2005 ; Lavelle et al, 2007 ; Alcover et al, 2017 ; Schuster et al, 2022a ). The implication for operationalizing the psychological contract is that, rather than treating an organization as a unitary contract maker, it seems reasonable to expect that employees may simultaneously hold distinct psychological contracts with the organization itself and with each of the different agents, leading to a multi-foci perspective of the psychological contract ( Marks, 2001 ; Conway and Briner, 2005 ; Schuster et al, 2022a ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight the multi-foci nature of social exchange relationships in which employees can simultaneously hold distinct perceptions toward organizations and each of the various constituencies contained within them ( Reichers, 1985 ; Marks, 2001 ; Lavelle et al, 2007 ). As such, it appears to be plausible that employees may simultaneously perceive an exchange relationship with the organization itself and any or all of these constituencies ( Marks, 2001 ; Conway and Briner, 2005 ; Lavelle et al, 2007 ; Alcover et al, 2017 ; Schuster et al, 2022a ). The implication for operationalizing the psychological contract is that, rather than treating an organization as a unitary contract maker, it seems reasonable to expect that employees may simultaneously hold distinct psychological contracts with the organization itself and with each of the different agents, leading to a multi-foci perspective of the psychological contract ( Marks, 2001 ; Conway and Briner, 2005 ; Schuster et al, 2022a ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of international assignment, more recent studies begin to explore the mediating role of the psychological contract ( Haak-Saheem et al, 2021 ; Koveshnikov et al, 2022 ). There are also studies examining the spillover effects of psychological contract breach on violation where expatriates have concurrent psychological contracts with the subsidiary and the headquarter ( Schuster et al, 2022a , b ). While contributing considerably to the field of expatriates’ psychological contracts, recent research has largely been outcome-oriented which focuses on how the evaluation of psychological contract state influences expatriate outcomes, mainly being addressed through a quantitative perspective.…”
Section: Introductionmentioning
confidence: 99%
“…HR managers reported that being open to new experiences, different work environments, cultures, and country-specific norms and standards was a key condition for successful digital knowledge transfer. Therefore, HR managers are advised to provide training to teach employees how to be open to and communicate efficiently via DCM and also include these considerations when considering the role of expatriates' psychological contracts (Schuster et al, 2022a(Schuster et al, , 2022b.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…On international assignments, MNCs temporarily relocate expatriates to a foreign subsidiary to transfer knowledge or coordinate business activities across borders (Harzing, 2001). In such a work arrangement, expatriates might form PCs with two entities in the same organization: their home (headquarters) and their host organization (subsidiary) (Kumarika Perera et al, 2017;Schuster et al, 2022). Compared to other multi-party work arrangements, prior research has argued that expatriates face additional PC challenges as they need to adjust to a new working and living environment (Bader et al, 2017;Black et al, 1991), leading to heightened expectations towards their home and host organization.…”
Section: Introductionmentioning
confidence: 99%
“…International assignments are distinct from other multi‐party settings because (1) multiple PCs are formed within the same firm and (2) working abroad demands high contributions from the employee beyond those in domestic settings (Kumarika Perera et al, 2017). Accordingly, expatriates may be particularly vulnerable to both unfulfilled psychological contracts and feelings of violation (Schuster et al, 2022) as they are highly dependent on their employers in order to realize important goals, a condition strengthening their reliance on employer fulfilment of its obligations (Rousseau et al, 2018). The strong emotions characterizing contract violation are more likely to be redirected and spill over to innocent parties if the parties involved are more strongly connected (Moody, 2008).…”
Section: Introductionmentioning
confidence: 99%